Outcomes of children with rhabdomyosarcoma treated with intensive chemotherapy, surgery, and radiotherapy through a period of protocol revision at a South African center, 1990–2010. Issue 3 (22nd September 2016) - Hendricks, Marc; Parkes, Jeanette; Pillay, Komala; Millar, Alastair; van Eyssen, Ann; Numanoglu, Alp; Davidson, Alan
Abstract: A total of 75 children with biopsy‐proven rhabdomyosarcoma were treated at our institution between 1990 and 2010. Five‐year overall survival (OS) for the entire cohort was 58.7%. OS by stage was as follows: Stage 1 (80%), Stage 2 (80%), Stage 3 (54.1%), and Stage 4 (38.5%). There was a trend to suggest that revision of treatment approaches improved crude survival over time: pre‐2003 (OS 42.1%); 2003–2005 (OS 50.0%); 2005–2010 (OS 60.8%).